Optimizing temperature threshold testing in small‐fiber neuropathy. Issue 6 (10th January 2015) - Bakkers, Mayienne; Faber, Catharina G.; Reulen, Jos P.H.; Hoeijmakers, Janneke G.J.; Vanhoutte, Els K.; Merkies, Ingemar S.J.
ABSTRACT Introduction: We examined optimization of a temperature threshold testing (TTT) protocol for patients with suspected small‐fiber neuropathy (SFN) to lessen the burden for both patients and technicians, without sacrificing accuracy. Methods: Data from 81 patients with SFN (skin biopsy and TTT abnormal) and 81 without SFN (skin biopsy and TTT normal) were used. Warm, cold, and heat pain sensation thresholds were determined bilaterally on the thenar eminence and foot dorsum by methods of limits and levels. Diagnostic accuracy was determined for various sensory modality combinations through comparative corresponding area under the receiver‐operator characteristic curves. Results: Assessment of warm and cold thresholds in all extremities by the method of levels showed the best discriminatory ability (area under the curve 0.95, sensitivity 84.2%, specificity 93.8%). Conclusions: These assessments are suggested for TTT examination in possible SFN patients. By applying this combination, the time needed for TTT can be reduced, maintaining diagnostic accuracy. Muscle Nerve51: 870–876, 2015